Folk theories of algorithms: Understanding digital irritation. (July 2021) - Ytre-Arne, Brita; Moe, Hallvard
This article draws on the framework of "folk theories" to analyze how people perceive algorithms in the media. Taking algorithms as a prime case to investigate how people respond to datafication in everyday media use, we ask how people perceive positive and negative consequences of algorithms. To answer our question, we conduct qualitative thematic analysis of open-ended answers from a 2019 representative survey among Norwegians, identifying five folk theories: algorithms are confining, practical, reductive, intangible, and exploitative. We situate our analysis in relation to different application of folk theory approaches, and discuss our findings in light of emerging work on perceptions of algorithms and critiques of datafication, including the concept digital resignation. We conclude that rather than resignation, digital irritation emerges as a central emotional response, with a small but significant potential to inspire future political action against datafication.